2017
DOI: 10.1148/radiol.2016160384
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Localizer Radiography Projection on Organ Dose at Chest CT with Automatic Tube Current Modulation

Abstract: Purpose To calculate the effect of localizer radiography projections to the total radiation dose, including both the dose from localizer radiography and that from subsequent chest computed tomography (CT) with tube current modulation (TCM). Materials and Methods An anthropomorphic phantom was scanned with 192-section CT without and with differently sized breast attachments. Chest CT with TCM was performed after one localizer radiographic examination with anteroposterior (AP) or posteroanterior (PA) projections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Second, the phantoms were positioned with the axial center of the phantom in the gantry isocenter based on the two orthogonal LRs. However, the center of attenuation depends on the z‐location and therefore does not coincide with the isocenter for the entire scan range, which makes ideal patient positioning a challenging task . Finally, instead of using real female and overweight phantoms, we added bolus material to the standard anthropomorphic male phantom, while the rest of its habitus remaining unchanged.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, the phantoms were positioned with the axial center of the phantom in the gantry isocenter based on the two orthogonal LRs. However, the center of attenuation depends on the z‐location and therefore does not coincide with the isocenter for the entire scan range, which makes ideal patient positioning a challenging task . Finally, instead of using real female and overweight phantoms, we added bolus material to the standard anthropomorphic male phantom, while the rest of its habitus remaining unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…The TCM technique is usually based on the width of the patient's body part and its attenuation obtained from the localizer radiograph (LR). Recent studies have suggested that inappropriate patient centering affects both image quality and patient dose when TCM is used . The reason behind this is that inaccurate centering of the patient in the CT gantry results in magnification of the acquired LR if the patient is positioned too close to the x‐ray source, leading to overestimation of the patient size and application of higher tube current than is actually necessary.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous researches reported the application of low-dose CT scan of chest, 19,20 in addition to study of low-dose CT scan of head and abdomen. 21,22 The study of low-dose CT scan of brain is limited, mainly due to the thicker skull and absorption.…”
Section: Low-dose Ct Scanmentioning
confidence: 99%
“…The authors calculated the size-specific dose estimate by using the scout images, when available. This approach has potential pitfalls because the vertical position of the patient and tube projection angle considerably influences patient size on scout images (9).…”
mentioning
confidence: 99%